2003
DOI: 10.1029/2002gl016690
|View full text |Cite
|
Sign up to set email alerts
|

Mineral dust sources in the surroundings of the north Indian Ocean

Abstract: We have used one year (1999) of Meteosat observations to monitor the dust activity in the arid and semi‐arid areas surrounding the North Indian Ocean. The method is based on the IDDI product derived from the infrared channel of the satellite. Dust sources are located according to a threshold on the IDDI and another on the surface wind speed. The global features of the dust activity in this area are in a good agreement with previous studies. Main dust sources are located in the Nubian desert, the Arabian penins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(84 citation statements)
references
References 15 publications
6
74
0
Order By: Relevance
“…However, regional characteristics of soil dust production, and transport and removal processes are less understood. Retrieval methods using infrared wavelengths (a technique used in this paper) have proved to be more suitable for studies on dust aerosols (Tanré and Legrand, 1991;Legrand et al, 2001;Leon and Legrand, 2003). Using NIMBUS data, Shenk and Curran (1974) have demonstrated that dust can be detected over arid regions using infrared radiance.…”
Section: Problems In Quantification Of Dustmentioning
confidence: 99%
“…However, regional characteristics of soil dust production, and transport and removal processes are less understood. Retrieval methods using infrared wavelengths (a technique used in this paper) have proved to be more suitable for studies on dust aerosols (Tanré and Legrand, 1991;Legrand et al, 2001;Leon and Legrand, 2003). Using NIMBUS data, Shenk and Curran (1974) have demonstrated that dust can be detected over arid regions using infrared radiance.…”
Section: Problems In Quantification Of Dustmentioning
confidence: 99%
“…Thus, it is essential to examine the number of dust events. The best and most common way of defining a dust event is by applying a threshold value for IDDI (Leon and Legrand, 2003). In our study we have used an IDDI value of 8 K to define a dust event.…”
Section: Quantification Of Wind Dependence Of Iddimentioning
confidence: 99%
“…Satellite remote sensing is well suited for a daily monitoring of the aerosol load (Kaufman et al, 2002;King et al, 1999). In the recent years several set of satellite data have fostered a comprehensive description of the temporal and spatial variability of different aerosol species, from anthropogenic aerosols ) to desert dust (Léon and Legrand, 2003). The monitoring of aerosols from space has also been widely used during this last decade for the evaluation of aerosol influence on global climate change through the impact on the Earth-atmosphere radiation budget (Boucher and Tanré, 2000;Bréon et al, 2002).…”
Section: Introductionmentioning
confidence: 99%